Facilitators and barriers to decision-making for hospital treatment among patients diagnosed with breast cancer in Dar es Salaam, Tanzania: A qualitative urban-based study. - Pascal Mkaka Dominic; Masunga K Iseselo; Raymond Athanas (PLOS Global Public Health)
Background Breast cancer is a major public health problem in both developed and developing countries and has become the second leading cause of death among women worldwide. The mortality may be related to delayed or inappropriate treatment decision-making among the diagnosed patients. Decision-making is an important determinant for successful treatment for patients diagnosed with breast cancer. In Tanzania, there is a lack of information in the context of facilitators and barriers to treatment decision-making after a breast cancer diagnosis. This study aimed to explore facilitators and barriers to treatment decision-making among cancer patients in Tanzania. Material and methods A descriptive qualitative design was employed to explore the facilitators and barriers to treatment decision-making at Ocean Road Cancer Institute in Dar es Salaam. A purposive sampling technique was used to recruit fourteen female patients diagnosed with breast cancer. Data were collected through in-depth, semi-structured interviews, which were audio-recorded. A thematic approach was used to analyze the data. Findings Two major themes emerged from the study findings, namely; facilitators to treatment decision-making such as patient understanding of treatment information, and healthcare providers' support. Barriers to treatment decision-making include the cost of treatment, uncertainty about cancer treatment, and religious healing. Conclusion This study found that practising decision-making for hospital treatment remains a challenge for patients diagnosed with breast cancer. Patients' understanding of treatment information and healthcare providers' support are the main tools that can facilitate decision-making. Sensitization activities on breast cancer treatment in the community and coverage of insurance should be advocated to promote decision-making for hospital treatment.